COOPERATION OF TEACHER AND STUDENT ON MUSIC WORK - Botirova Xilola Tursunbaevna (Universitas Brawijaya, 2020)
This article attempts to highlight the enormous challenges faced a teacher. The actuality of the article is that it focuses on the attention of art in the education and cases of implementation of the projects of decree. We are not exaggerating to say that this scientifically-based article aims to highlight the President's initiatives and efforts. At the same time, the focus on the attention to the teacher and his spare ways were justified